Proteins as possible targets for antitumor metal complexes: biophysical studies of their interactions - Chiara Gabbiani (Premio Tesi di Dottorato, 2009)
There is considerable interest today for the reactions of anticancer metallodrugs with proteins as these interactions might feature processes that are crucial for the biodistribution, the toxicity and even the mechanism of action of this important group of anticancer agents. Valuable structural and functional information on these adducts could be derived from several biophysical studies mainly relying on the application of X-ray diffraction and ESI MS techniques. The structural and functional information achieved on the respective metallodrug-protein adducts allowed us to identify some general trends in the reactivity of anticancer metallodrugs with protein targets.